Ligand-induced control of photoconductive gain and doping in a hybrid graphene-quantum dot transistor - Turyanska, Lyudmila; Makarovsky, Oleg; Svatek, Simon A.; Beton, Peter H.; Mellor, Christopher J.; Patanè, Amalia; Eaves, Laurence; Thomas, Neil R.; Fay, Michael W.; Marsden, Alexander J.; Wilson, Neil R. (Wiley-VCH, 2015)
In graphene devices decorated with a layer of near-infrared colloidal PbS quantum dots (QDs), the choice of the QD capping ligands and the integrity of the QD layer have a strong influence on the doping, carrier mobility, and photoresponse. By using short (<1 nm) capping ligands, the photoresponsivity of the graphene devices is enhanced up to 109 A W−1.